What Genomic Sequencing Can Offer Universal Newborn Screening Programs - Powell, Cynthia M. (The Hastings Center report, 2018)
Massively parallel sequencing, also known as next-generation sequencing, has the potential to significantly improve newborn screening programs in the United States and around the world. Compared to genetic tests whose use is well established, sequencing allows for the analysis of large amounts of DNA, providing more comprehensive and rapid results at a lower cost. It is already being used in limited ways by some public health newborn screening laboratories in the United States and other countries—and it is under study for broader and more widespread use, including as a core part of newborn screening programs. Sequencing technology has the potential to significantly improve these essential public health programs. For many of the conditions that newborns are already screened for, sequencing can return more specific and more sensitive results. The technology could also enable newborn screening programs to expand the list of rare pediatric conditions that they look for, thereby identifying more infants who can benefit from immediate care.